Limitations of the European barrier crash testing regulation relating to occupant safety. (December 2019) - Chell, Jasper; Brandani, Carola Elea; Fraschetti, Stefano; Chakraverty, Joe; Camomilla, Valentina
Highlights: The European regulation EN-1317 has the potential to certificate unsafe barriers. Indices based on vehicle kinematics are inaccurate predictors of head kinematics. Acceleration severity index may characterise risky cockpit deformations as positive. Abstract: The safety of roadside restraint systems in Europe is ensured by the EN 1317 regulation. The ability of the barrier to mitigate injury to the occupants of vehicles is tested according to two occupant injury metrics: Acceleration Severity Index (ASI) and Theoretical Head Impact Velocity (THIV). Both metrics aim to predict occupant head injury from vehicle kinematics, despite the potential to easily measure actual head kinematics from instrumented Anthropomorphic Test Dummies, a non-instrumented version of which is already required according to the regulation. Retrospective data provided by AISICO S.r.l. for 33 certificated barrier tests, where acceleration of the dummy's head had also been recorded, were re-analysed. ASI and THIV were compared with Head Injury Criterion (HIC15 ) and Neck injury Criterion (Nij ), as well as corresponding Real Head Impact Velocity (RHIV) values. Three barriers presented HIC15 values above the threshold used in crashworthiness testing, two of which corresponded to fatal injury according to the Abbreviated Injury Scale. One barrier presented an Nij value corresponding to a 30% risk of neck injury. RHIV values were above the regulation threshold in 15% of tests, but were not significantly different from the corresponding THIV values. It was concluded that vehicle kinematics do not accurately predict head kinematics during barrier testing. The presented data indicate the current EN 1317 regulation was not capable of detecting all potential dangerous outcomes, with the potential to underestimate occupant risk. Further investigation is necessary to devise suitable indices based on actual head and neck data. These data would be obtained from a dummy instrumented with both a head accelerometer and neck load cell and, possibly, a gyroscope. To consistently test the true worst-case scenario, the tested side window should be closed and non-reinforced.